2021
DOI: 10.3390/ma14237251
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Polyetherimide Melt-Extruded Fibers Modified by Carbon Nanoparticles

Abstract: The fibers based on thermoplastic partially crystalline polyetherimide R-BAPB modified by vapor grown carbon nanofibers (VGCF) were prepared by melt extrusion, exposed to orientational drawing, and crystallized. All of the samples were examined by scanning electron microscopy, X-ray scattering, and differential scanning calorimetry to study how the carbon nanofiller influences on the internal structure and crystallization behavior of the obtained R-BAPB fibers. The mechanical properties of the composite R-BAPB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
3
4
0
Order By: Relevance
“…However, the almost constant level of the crystallinity degree cannot be a guarantee of the constant level of the strength of the material doped by the nanoparticles, since the quality of the amorphous regions’ organization will play more important role. A similar effect has been observed earlier on the other polymer composites [ 12 ].…”
Section: Resultssupporting
confidence: 89%
“…However, the almost constant level of the crystallinity degree cannot be a guarantee of the constant level of the strength of the material doped by the nanoparticles, since the quality of the amorphous regions’ organization will play more important role. A similar effect has been observed earlier on the other polymer composites [ 12 ].…”
Section: Resultssupporting
confidence: 89%
“…The sharpest decrease is observed for the pure R-BAPB fibers. Possible explanations for this phenomenon are consistent with the assumption 33 that the crystallites formed in the R-BAPB fibers are weakly connected to each other through molecular chains and, thus, the number of the load-bearing macromolecules is too small to withstand the applied stress in strength and deformation before fracture during crystallization annealing of oriented fibers.…”
Section: Mechanical Properties Of Pi Fiberssupporting
confidence: 72%
“…In our recent work, it was shown that the addition of vapor grown carbon nanofibers (VGCF) into R-BAPB type PI is promising for changes in the structure and thermomechanical properties of meltextruded fibers. 33,34 As the continuation of this cycle of work, it would be interesting to analyze the changes in the properties of the composite fibers based on semicrystalline PIs as R-BAPB upon the introduction of SWCNTs into them. The aim of this work is a detailed study of changes in the structure, thermal and mechanical properties of the fibers based on R-BAPB type PI modified with the SWCNTs, with further orientational thermal drawing and additional heat treatment, resulting in crystallization of the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymeric materials have directly or indirectly become an integral part of our lives in recent years, as they are widely used in various areas of our daily life. A group of materials that consist of a polymer matrix and intentionally dispersed fillers of nanometer size (up to 100 nm) are hybrid systems that are defined as polymer nanocomposites (NCs).The efforts of many scientists in recent years have also been aimed at achieving a synthesis of different types of polymer nanocomposites and understanding their basic principles in determining their properties for application in a wide range of fields [ 1 , 2 , 3 , 4 , 5 ]. Many large-scale scientific studies carried out in recent years clearly show that when the nanofillers are uniformly dispersed in a polymer matrix, the NCs exhibit remarkably better electrical, thermal [ 6 , 7 ], mechanical [ 8 , 9 , 10 ] properties compared with a pure polymeric organic matrix or micro composites [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%